Comparison of Laparoscopic and Open Surgery for Women With Early-Stage Epithelial Ovarian Cancer - Ran, Xuting; He, Xinlin; Li, Zhengyu (Frontiers in Oncology, 2022)
Objective: This study aimed to evaluate the oncologic outcomes between laparoscopy and laparotomy in the management of early-stage ovarian cancer patients. Methods: We performed an observational study of women diagnosed with International Federation of Gynecology and Obstetrics (FIGO) 2014 stage I ovarian cancer who underwent surgery in West China Second University Hospital from 2012-2020. Patients who received adjuvant chemotherapy before surgery, those with non-epithelial histopathological types, or those with insufficient data were excluded. Data of consecutive patients treated by laparoscopy were matched 1:2 with a cohort of patients undergoing open surgery using a propensity score matching. The operative and survival outcomes among the matched cohorts were examined using the Kaplan-Meier method. Results: Among 200 eligible patients, 74 patients undergoing laparoscopy were compared with a cohort of 126 patients undergoing open surgery. Baseline characteristics were similar between groups after matching. Patients undergoing laparoscopy experienced longer operative time (P = 0.001), shorter hospital stay (P < 0.001), and lower blood loss (P = 0.001) than patients undergoing open surgery. The median (range) follow-up period was 43.0 (38.8-47.2) and 45.0 (36.0-54.0) months for case and control, respectively (P < 0.001). There are no significant differences in progression-free survival (P = 0.146, log-rank test) and overall survival (P = 0.142, log-rank test) between two groups. Conclusions: There is no difference in prognosis between laparoscopic and open surgery in women with stage I epithelial ovarian cancer. Laparoscopic treatment of early-stage ovarian cancer is safe and feasible for stage I epithelial ovarian cancer patients.